An augmented lagrangian pattern search method for optimal WWTP designs - Espírito Santo, I. A. C. P. (2007)
This paper describes a derivative-free method to solve a non-linear constrained optimization problem that arises from the mathematical formulation of an activated sludge system of a wastewater treatment plant (WWTP), in which the objective is to minimize the investment and operation costs. The method relies on an augmented Lagrangian function to penalize infeasible solutions and uses the original Hooke and Jeeves pattern search method for solving bound constrained subproblems. The experimental results are very promising and give economically attractive WWTP designs.